2013
DOI: 10.1111/j.1524-4725.2012.02579.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Squamous Cell Carcinomas and Eruptive Keratoacanthomas in an Arc Welder

Abstract: The authors have indicated no significant interest with commercial supporters. W e report an arc welder who developed 51 squamous cell carcinomas (SCCs) on the dorsal upper extremities after 10 years of unprotected arc welding. SCCs began to appear 27 years after he started welding. Mohs surgery and acitretin were necessary to control his disease. Case ReportA 52-year-old Caucasian man, Fitzpatrick skin type III, was referred to our clinic in 2007 for three eruptive SCCs adjacent to two recent surgical sites i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…Four case reports indicated that the welder or an assistant had not worn proper protective clothing such as shields and gloves. [15][16][17][18] In addition, five case-control studies have been published concerning the potential link between welding and skin cancer ( Table 2). 9,[19][20][21][22] Four of the five studies did not find an increased prevalence of skin cancer in welders.…”
Section: Skin Cancer Risk In Weldersmentioning
confidence: 99%
See 1 more Smart Citation
“…Four case reports indicated that the welder or an assistant had not worn proper protective clothing such as shields and gloves. [15][16][17][18] In addition, five case-control studies have been published concerning the potential link between welding and skin cancer ( Table 2). 9,[19][20][21][22] Four of the five studies did not find an increased prevalence of skin cancer in welders.…”
Section: Skin Cancer Risk In Weldersmentioning
confidence: 99%
“…Skin cancer type n Currie and Monk, 2000 16 Basal cell carcinoma 3 Donoghue and Sinclair, 1999 17 1 Ewing et al, 1971 23 1 Goetze and Elsner, 2014 24 1 Ratner et al, 2001 25 1 Currie and Monk, 2000 16 Squamous cell carcinoma 2 Wolfe et al, 2013 18 1 Caroe TK et al, 2013 26 Unknown or mixed types 5 Dixon et al, 2007 15 1 Similarly, Zamanian et al 19 found no significant differences in skin cancers in welders vs. nonwelders, yet the mean age of welders in their study was only 36 years. The patient populations in these studies may have been too young to appropriately investigate skin cancer risk.…”
Section: Referencementioning
confidence: 99%
“…Another casuistic study reported a woman who had presented with numerous SCC on her hands and forearms after assisting her son with welding business (Dixon 2007 ). Three other case reports depicted welders developing SCC and BCC after unprotected arc welding (Donoghue and Sinclair 1999 ; Kristensen and Sorensen 2015 ; Wolfe et al 2013 ). Although casuistic studies have demonstrated a potential risk of NMSC due to welding, the epidemiological evidence for an association between long-term arc welding and skin cancer is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The suspicion linking welding with skin cancer originates from reports. Several case reports have been published of BCC and SCC occurring after years of arc welding (Currie and Monk 2000 ; Dixon 2007 ; Donoghue and Sinclair 1999 ; Kristensen and Sorensen 2015 ; Wolfe et al 2013 ). Currie et al reported on five cases of welders with non-melanoma skin cancer (NMSC) whose mean age at presentation was 52 years (Currie and Monk 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 20 cases of squamous cell carcinoma arising in a tattoo are described in the literature. 7 , 39 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 The cases were reported most frequently in males (50%) followed by females (40%) ( Table I ). Most of the lesions were located on the extremities (71.4%) ( Table I ).…”
Section: Resultsmentioning
confidence: 97%